2021
DOI: 10.1016/j.toxrep.2021.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of metformin and gallic acid on inflammation, antioxidant status, endoplasmic reticulum (ER) stress and glucose metabolism in fructose-fed streptozotocin-induced diabetic rats

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 82 publications
(89 reference statements)
2
8
0
Order By: Relevance
“…Furthermore, metformin can suppress Ang II-induced cardiovascular remodeling by reducing AT 1 R expression in cardiovascular cells 55 . The antioxidant and anti-inflammatory effects of metformin in the present study have been demonstrated by previous observations in fructose-fed streptozotocin-induced diabetic rats 56 . Metformin has also been shown to enhance PPARγ expression in MS rats 54 and activate the Nrf2/HO-1 signaling pathway to alleviate oxidative stress in type 2 diabetic osteoporosis 57 .…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, metformin can suppress Ang II-induced cardiovascular remodeling by reducing AT 1 R expression in cardiovascular cells 55 . The antioxidant and anti-inflammatory effects of metformin in the present study have been demonstrated by previous observations in fructose-fed streptozotocin-induced diabetic rats 56 . Metformin has also been shown to enhance PPARγ expression in MS rats 54 and activate the Nrf2/HO-1 signaling pathway to alleviate oxidative stress in type 2 diabetic osteoporosis 57 .…”
Section: Discussionsupporting
confidence: 86%
“…The pancreas and liver of diabetic rats were examined after administering metformin and GA. Outcomes showed that metformin and GA decreased the levels of IL-6 and TNF-α, and the expression of ATF4. Results of the study validated that the combination of GA and metformin is more effective than metformin alone [ 119 ]. Furthermore, another study validated that andrographolide and gallic acid synergistically reduce the level of blood glucose [ 120 ].…”
Section: Pharmacological Efficacy Of Tamarix Aphyllamentioning
confidence: 93%
“…Substantially reduced blood triglycerides have also been reported in diabetic rats [111,122,123,132]. In addition, enhanced antioxidant capacity in liver, pancreas [119,123], blood [125], and brain [126] have been observed. It is of importance to note that phenolic compounds also ameliorated diabetic nephropathy [111] and cognitive decline [112,127].…”
Section: Intracellular Metabolites and Biomarkers Altered In Response...mentioning
confidence: 99%
“…It is of importance to note that phenolic compounds also ameliorated diabetic nephropathy [111] and cognitive decline [112,127]. Importantly, phenolic acids and flavonoids lowered levels of interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α) in liver, pancreas [119], and brain [126,127], suggesting their importance in the control of inflammation. These mechanisms played important roles in increasing insulin sensitivity and reversing insulin resistance, ameliorating the diabetes condition and related complications.…”
Section: Intracellular Metabolites and Biomarkers Altered In Response...mentioning
confidence: 99%